2019
DOI: 10.1177/1932202x19828744
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Postsecondary Success for Low-Income and High-Potential Students: A Systematic Review

Abstract: Research indicates that high-potential students from low-income backgrounds have decreased educational attainment and success in college compared with their higher income peers. The purpose of this review is to synthesize the interventions that support postsecondary success for this group. Using a systematic review protocol, we identified five categories of support for these students: a summer intervention, advanced coursework, financial aid, college information, and a program that provides year-round supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Evidence supports this criticism, with family and peer supports associated with retention and completion (Juang et al , 2016; Mitchall and Jaeger, 2018). A central reason for studying social supports is because they are associated with socioemotional health, a key determinant of postsecondary persistence (D’Amico Guthrie and Fruiht, 2020) that is responsive to intervention (Renbarger and Long, 2019). In this study, we examined college students' family and peer academic supports in relation to important academic motivation and first-semester grade point average.…”
mentioning
confidence: 99%
“…Evidence supports this criticism, with family and peer supports associated with retention and completion (Juang et al , 2016; Mitchall and Jaeger, 2018). A central reason for studying social supports is because they are associated with socioemotional health, a key determinant of postsecondary persistence (D’Amico Guthrie and Fruiht, 2020) that is responsive to intervention (Renbarger and Long, 2019). In this study, we examined college students' family and peer academic supports in relation to important academic motivation and first-semester grade point average.…”
mentioning
confidence: 99%
“…In comparison to previous reviews (Contreras, 2011; Renbarger & Long, 2019) that have investigated WP outreach for low socio‐economic students who were gifted, this study captures all studies that are trying to target any students who experience barriers to progression to higher education because of socio‐economic disadvantage. Younger et al (2019) also conducted a systematic review of the literature; however, their searches were conducted in 2012 and 2013.…”
Section: Methodsmentioning
confidence: 99%
“…She argues that programmes serving target groups should attempt to include such things as financial aid workshops, extracurricular support and mentorship (Contreras, 2011). More recently, Renbarger and Long (2019) investigated WP interventions for low-income students; however, only those interventions that targeted students who were considered academically gifted were included in the inclusion criteria. Their review indicated that WP programmes such as a summer intervention, advanced coursework, financial aid, college information and a programme that provides year-round supports can be effective in supporting low-income, gifted students to access college.…”
Section: Introductionmentioning
confidence: 99%
“…But racial/ethnic and socioeconomic disparities in the distribution of qualifying scores are also likely to be associated with structural differences between schools that result in inadequate academic preparation for many black, Latino, and low-income students. Consistent with Renbarger and Long (2019), Kolluri (2018) has suggested that poor performance in AP may be the result of poorly delivered content, particularly in schools in low-income neighborhoods, which often struggle to attract and retain high-quality teachers (Clotfelter et al, 2006; Lankford et al, 2002; U.S. Department of Education, Office for Civil Rights, 2014).…”
Section: The Promise Of Advanced Placementmentioning
confidence: 95%